The introduction of nursing led bubble-CPAP in a neonatal unit in Ghana: A 32-month observational report - Lawrence Fordjour; Lisa Washburn; Elizabeth Darko; Vivian Koffie; Fauziya Rabiu; Nana Okai Brako; Nana Sereboe; Corey Seidel; Bryan King; Darren Bodkin; Medge Owen (Elsevier, 2023)
Neonatal deaths account for nearly 50 % of under-five deaths in Ghana with prematurity as the leading factor. Bubble continuous positive airway pressure (bCPAP) is important in treating respiratory distress (RD) associated with prematurity but its use in Africa is challenging. There is limited equipment to care for vulnerable newborns and insufficiently trained healthcare staff. This 32-month observational study describes the characteristics and outcomes of bCPAP treated newborns as a nursing led intervention at a regional referral hospital in Ghana. In May 2014, bCPAP was introduced to newborn intensive care unit (NICU) nursing staff. Three bCPAP machines and supplies were donated by Medical Technology Transfer and Services (MTTS). A training program provided learning opportunities for US-based and Ghanaian staff. Locally collected data included: NICU census, staffing, admitting diagnosis, birth weight, gestational age, Apgar scores, antenatal corticosteroid administration, days on bCPAP, and survival. From May 2014 to December 2016, 189 newborns received bCPAP. The mean ± SD (range) gestational age was 30.0 ± 4.2 (24-42) weeks, birth weight was 1.5 ± 0.7 (0.5-4.25) kg, and bCPAP duration was 3.2 ± 3.3 (0-14) days. In 155 (82.0 %), the admission diagnosis was prematurity with RD. Survival in this group was higher compared to other diagnostic categories and improved as birthweight increased (p < 0.05). Overall, 57.8 % of bCPAP treated newborns survived, but survival decreased during the last 12 months for newborns < 1.5 kg. This study supports the long-term sustainability of a nursing-led bCPAP program in Africa, but positive outcomes may be compromised by staffing, equipment, and resource limitations.